Three cycles of AC chemotherapy regimen increased oxidative stress in breast cancer patients: A clinical hint - Mostafa Taherkhani; Soleiman Mahjoub; Dariush Moslemi; Ahmad Karkhah (Babol University of Medical Sciences, 2017)
Background: Recent studies have suggested the importance of oxidant/antioxidant status in initiation and progression of breast cancer. The aim of this study was to evaluate oxidative stress markers in breast cancer patients before and after 3 cycles of chemotherapy with adriamycin and cytoxan (AC). Also, in this study the effect of age and the stage of disease on oxidative stress markers were compared and evaluated. Methods: This study included 60 women with newly diagnosed stage II-III breast cancer who underwent chemotherapy with AC as the therapy-first strategy after surgery. Serum samples were obtained before treatment and after the third chemotherapy. Then, serum total antioxidant status (TAS) and malondialdehyde (MDA) as lipid peroxidation marker were analyzed. Moreover, the effects of the subject’s age and clinical disease stage were investigated. Results: A concurrent significant increase in MDA (p<0.001) and a significant decrease in TAS (p<0.001) were also observed after 3 cycles of AC chemotherapy. In addition, some changes were found in the status of oxidative stress markers which were associated with age and clinical disease stage. Conclusion: Our data indicated that chemotherapy with AC increase the oxidative stress in breast cancer patients. The present study indicated that higher stages of the breast cancer are associated with significant increases of oxidative stress markers.